2007
DOI: 10.1159/000107934
|View full text |Cite
|
Sign up to set email alerts
|

A New in vitro Model to Study the Relationship of Gap Size and Secondary Caries

Abstract: Objectives: To investigate the relationship of gap size and secondary caries in a newly developed secondary caries microbial model that permits adjustment of the gap between the tooth and a restoration. Methods: Tooth-resin-matrix composite specimens were mounted on gap-model stages with a gap size of 50 or 500 µm in experiment 1, and 0, 25, 250, or 1,000 µm in experiment 2. They were attached to plastic Petri plates, gas-sterilized and then incubated in a microbial caries model (with Streptococcus mutans TH16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
116
3
10

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(132 citation statements)
references
References 59 publications
3
116
3
10
Order By: Relevance
“…Both aspects deliver the rationale for the hypothesis that wider gaps allow the development of larger secondary wall lesions. However, the influence of the gap width is still a matter of debate, and conflicting results can be found in the literature [14,16,[21][22][23]. Also, recent investigations in vivo and on extracted teeth were often criticised because the diagnosed caries in the tooth restoration interface was not supposed to be a secondary caries lesion but either an inner part of the outer lesion or a residual caries [12,21,24,25].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Both aspects deliver the rationale for the hypothesis that wider gaps allow the development of larger secondary wall lesions. However, the influence of the gap width is still a matter of debate, and conflicting results can be found in the literature [14,16,[21][22][23]. Also, recent investigations in vivo and on extracted teeth were often criticised because the diagnosed caries in the tooth restoration interface was not supposed to be a secondary caries lesion but either an inner part of the outer lesion or a residual caries [12,21,24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on effects of different gap widths on the extent of caries lesion have been conducted in vivo [13,21], on extracted teeth [15], and in vitro with different bacterialbased caries models [14,16]. Each of these experimental designs has its advantages and disadvantages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This geometric setup was replicated in an improved mechanical device several years later against a block of resin composite [140]. The authors concluded that there were clear correlations between gap size and demineralized lesions in the contact zone, which they regrettably named "wall lesion".…”
Section: Artificial Caries-like Lesions Adjacent To Restorationsmentioning
confidence: 99%